Spirometric evaluation of pulmonary functions of medical students in Nepal - Banskota Nepal, Grishma; Das, PKL; Bhaila, A (Asian Journal of Medical Sciences, 2014)
Background: Spirometry is vital in screening, diagnosing and monitoring of patients in clinical respiratory medicine. The interpretations of these results depend on comparison with reference values derived from a pool of normal healthy population, which are age, weight, height, gender and ethnicity dependant. Objectives: To establish normative data of lung function indices (FVC, FEV1, FEV1/FVC, PEFR and MVV) of healthy adult persons and to find correlation of these data, if any, with age, height, weight and BMI. Methods: Participants (n=174, mean age 19.60±1.177 yrs, height 161.87±8.572 cm, weight 58.65±11.190 kg and BMI 22.28±3.159 kg/m2) were recruited from KIST medical college. Spriometry was performed and data were grouped according to age, height, weight, BMI and gender. Results: The mean FVC, FEV1, PEFR and MVV of males (3.58 ±0.7241 L, 3.34±0.61L, 8.41±1.20L/sec and 141.45±18.54L/min respectively) were significantly higher than that of females (2.52±0.50L, 2.44±0.44L, 6.72±0.82L/sec and 106.93±12.49L/min respectively). However, FEV1/FVC ratio was statistically similar in males and females. FVC and FEV1 were positively correlated with height and weight in females. PEFR showed correlation with weight and BMI and MVV showed correlation with weight in females. In males, FVC showed positive correlation with height, weight and BMI. FEV1 and MVV showed maximum correlation with height of male students. Conclusions: Significant increased in PFT parameters were observed in male as compare to female. PFT parameters were mainly influenced by body height and weight in both sexes, so on this basis, a prediction equation was established for Nepalese population. Asian Journal of Medical Science, Volume-5(3) 2014: 82-86 http://dx.doi.org/10.3126/ajms.v5i3.9352